ANALISIS PREFERENSI CALON PENABUNG SIMPANAN PEMUDA (SIMUDA) DI LEMBAGA KEUANGAN PERBANKAN - Towaf Totok Irawan (Universitas Pakuan, 2020)
The purpose of this study is to describe the preferences of potential Simuda savers for prizes given by banks. This research was conducted on 300 respondents consisting of 100 Student Savers (Simple), 100 students and 100 employees. The sampling technique in this study is nonprobability sampling with a sampling quota, with data analysis techniques using descriptive statistics. The results of this study showed 50% of respondents expressed an interest in saving on Simuda products, with prizes in the form of vouchers, direct prizes, sweepstakes, and the benefits of Simuda cards.